Temporal changes in the surgical management of patients with tetralogy of Fallot in Denmark: a nationwide cohort study. (6th January 2023) - Gröning, Mathis; Smerup, Morten Holdgaard; Nielsen, Dorte Guldbrand; Nissen, Henrik; Munk, Kim; Mortensen, Ulrik Markus; Andersen, Helle; Engholm, Morten; Bjerre, Jesper; Vejlstrup, Niels; Juul, Klaus; Søndergaard, Eva Vad; et al.
Abstract: OBJECTIVES: To assess temporal changes in the surgical management of patients with tetralogy of Fallot including the timing of interventions, surgical techniques, reinterventions and survival in a nationwide cohort. METHODS: Patients with tetralogy of Fallot in Denmark were divided into 3 eras based on their year of birth: early (1977–1991), intermediate (1992–2006) and late (2007–2021). RESULTS: The cohort consisted of 745 patients. Median follow-up was 21.2 years (13.7–30.5). There was a temporal trend towards less shunt palliation (–0.3% per year, 95% CI –0.05 to –0.1). Median age at intracardiac repair was 2.9 years (1.8–5.0), 0.8 years (0.5–1.3) and 0.5 years (0.4–0.7) ( P < 0.001) in the early, intermediate and late era, respectively. There was a temporal trend towards less valve-sparing repair (–0.7% per year, 95% CI –0.5 to –1.0) and more repair with transannular patches (0.7% per year, 95% CI 0.5–1.0). Survival at 10 years was 79% (64–76), 90% (87–93) and 95% (92–98) ( P < 0.001) and pulmonary valve replacement within the first 10 years after intracardiac repair was performed in 3% (1–6), 12% (8–16) and 21% (13–29) ( P < 0.001) in the early, intermediate and late era, respectively. CONCLUSIONS: There was a temporal trend towards less shunt palliation and intracardiac repair at a younger age with more use of transannular patches. While survival throughout childhood and adolescence has improved, more patients undergo pulmonary valve replacement during the first 10 years after intracardiac repair. Abstract : The first successful shunt palliation in a patient with tetralogy of Fallot (ToF) was performed in 1944, the first successful right ventricular outflow tract (RVOT) dilatation and pulmonary valvotomy were reported around 1948 and the first successful intracardiac repair was achieved in 1954 [1–3].